Flipbook Media Assisted by Local Wisdom to Improve Learning Outcomes Narrative Text for Fourth Grade Elementary School - Nichollas Bernard Steven Julian Totti; Sukarir Nuryanto (Journal of Education Reseach and Evaluation, 2024)
The implementation of an independent curriculum in Indonesian language learning was still less effective in the applied and used of learn media, resulted in a lack of enthusiasm, motivation, and low student learned outcomes. This research aims to developed learning media in the form of flipbooks with the help of the local wisdom of Geopark Karangsari, to identified the effectiveness of developed flipbook media with the help of local wisdom of Geopark Karangsari to improve learning outcomes for class IV narrative texts. This research used Research and Development (R&D) with the ADDIE model which consists of five stages. This research collecteds data using test techniques in the form of pretest and posttest; and non-test techniques in the form of observation, interviews, questionnaires, and documentation. There are two stages of data analysis techniques used in this research, namely initial data analysis and final data analysis. Initial data analysis contains normality tests and homogeneity tests of learning outcomes before and after using flipbook media. Meanwhile, the final data analysis contains a t-test and n-gain test on learning outcomes before and after using flipbook media. The results of this researched prove that flipbook media assisted by local wisdom from Geopark Karangsari improves narrative text learning outcomes for class IV SD. The increased in narrative text learned outcomes is shown by the n-gain test of 0.66 with an average difference of 26.52 which is categorized as medium.